Mapping the Linguistic Landscape of Medan, Indonesia and Kuala Lumpur, Malaysia: The Case of Shop Signs - Dewi Nurmala; Ayu Melati Ningsih; Devendran A/L Ramachandran (English Department - University of Sultan Ageng Tirtayasa, 2026)
This study investigated the linguistic landscape of shop signs in Medan and Kuala Lumpur. The objectives focus on three points, namely, the language choice, multilingual writing, and visual aspects of shop signs. The study employed mixed-method design with data of shop signs pictures in Medan and Kuala Lumpur. Data collected using photographic documentation of shop signs. The shop signs were analysed by combining linguistic landscape analysis with language choice, multilingual writing and visual semiotic analysis. The findings identified three points. First, different language choices in Medan and Kuala Lumpur. Most language choices in Medan are monolingual and in Kuala Lumpur are bilingual and multilingual. Second, complementary multilingual writing is predominantly found in Medan while dominantly found in Kuala Lumpur. Third, most the text position as main information on shop signs in Medan are in the middle of the signs or under the signboard while in Kuala Lumpur, the text position as main information on shop signs is in the top right on signboard. The use of fonts and colours of both countries are still the same. The conclusion of the study is that linguistic diversity reflects the multicultural populations in both cities and the importance of using languages to appeal to a wide customer base.